This New Earthgazing VR Experience Will Help Astronauts Cope With Loneliness In Space - Sajwar, Rameesha (Wonderful Engineering, 2021)
Advertisement Researchers in Simon Fraser University’s iSpace Lab created a virtual reality experience called Earthgazing which will be tested as part of SIRIUS 2021, a study launching this month in Moscow. This experiment will be one of the 70 that will be done on six people’s crew. They will be spending eight months in a facility, […]
Keywords: mediaCoverage; proj--SIRIUS-earthgazing-newscoverage